Tanggap Tanaman Kedelai terhadap Inokulasi Rhizobium dan Asam Indol Asetat (IAA) pada Ultisol Darmaga - Rina D. Ningsih; Iswandi Anas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
Some of rhizobacteria have been known to stimulate the growth of some crops through their fitohormon (IAA = indole acetic acid). Those rhizobacteria can stimulate the development of epidermis cells formation at root hair  site and increase the infection sites to increase the nodulation and N2 fixation. The aims of this study were to study the effect of Rhizobium strains inoculation and indole acetic acid (IAA) application on crop growth, root nodulation. and N, P uptake of soybean on the Ultisols. The greenhouse experiment used Completely Randomize Design (CRD) with four replications. The treatments were: I) Without inoculation (blank), 2) 100 ppm N application, 3) 0.4 ppm IAA application, 4) Inoculation of Rhizobium 1004 (106), 5) Inoculation of Rhizobium 1004 (I05) + IAA, 6) Inoculation of  Rhizobium RD-20 (104), 7) Inoculation of Rhizobium RD-20 (106), 8) Inoculation of Rhizobium SNI-2 (106). 9) Inoculation of Rhizobium SNI-2 106 + IAA. Result of the experiment indicated that inoculation of Rhizobium and IAA application increased crop growth, nodulation, and nutrient uptake of soybean. Inoculation of Rhizobium I004(106). RD-20(104)R, D-20(I06),S NI-2(I06), and IAA 0.4 ppm increased dry weight of crop by 33.5%,37.8,17.3%,35.1%,and 3.8% respectively compared to blank. Application of IAA at Rhizobium inoculation treatment of SNI-2(106) and 1004(106i)n creased dry nodule weight on soybean 40.9%, and 55.7 % respectively compared to without IAA application.